(untitled) (Anwer Khan Modern Medical College Journal, 2014)
Fujimoto (KD) disease or histiocytic necrotizing lymphadenitis is a rare, benign, self limiting cervical lymphadenitis of unknown etiology. Since Tubercular lymphadenopathy is the commonest cause for chronic cervical lymphadenopathy in developing and tropical country like Bangladesh. Occasionally it is misdiagnosed as TB and subsequently shows unresponsiveness to ATT. As a result the morbidity increases and cost of antitubercular treatment (ATT) in wrong diagnosed case is enormous. We report a similar case of misdiagnosis. We report a 26 year old lady who reported with history of right sided neck pain and fever since last 2 months. Clinical examination revealed enlared right sided lymph nodes in the neck. Fine needle aspiration cytology revealed features suggestive of granulomatous lymphadenitis. The case was suspected to be tuberculosis and anti-tubercular therapy (ATT) was started immediately. Since the patient did not respond, lymph node biopsy was done and the histological features suggested the diagnosis of Kikuchi’s disease. She did well after recommended treatment. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21134 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 51-53